Anionically functionalized ultramicroporous materials, methods of making and using the same

CN118236991BActive Publication Date: 2026-10-23ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211668921.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2026-10-23
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

这两个专利技术获得了较好的分离效果,但仍有待提升

Benefits of technology

[0022] The anion-functionalized ultraporous material provided by this invention can be applied to the selective adsorption and separation of C5-C8 alkane isomers. It can preferentially adsorb low-octane alkanes (straight-chain and single-branched alkanes) to obtain pure high-octane alkanes (multi-branched alkanes), thereby efficiently improving the octane number of gasoline.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118236991B_ABST
    Figure CN118236991B_ABST
Patent Text Reader

Abstract

The application discloses an anion functionalized ultra-microporous material and a preparation method and application thereof. The anion functionalized ultra-microporous material is self-assembled by 3,3'-dipyridyl organic ligand, inorganic fluorine-containing anion and metal ions through coordination bonds, wherein the metal ions are any one of Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ ; and the inorganic fluorine-containing anion is any one of SiF6 2‑ , GeF6 2‑ , ZrF6 2‑ , SnF6 2‑ , TiF6 2‑ , NbOF5 2‑ , TaOF5 2‑ , WO2F4 2‑ , MoO2F4 2‑ . The anion functionalized ultra-microporous material can be prepared by an interface diffusion method and a hydrothermal method, raw materials are easy to obtain, and the preparation method is simple. The anion functionalized ultra-microporous material has a large adsorption capacity for low-octane straight-chain and single-branched-chain alkanes, but has a small adsorption capacity for high-octane double-branched-chain alkanes, and can be used for separation of isomerized oil to obtain high-octane gasoline.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functionalized materials, specifically to an anion-functionalized ultraporous material, its preparation method, and its applications. Background Technology

[0002] C5-C8 low-carbon alkane isomers are important raw materials for producing high-octane clean gasoline. The C5-C8 hydrocarbons obtained through heavy naphtha isomerization are typically a mixture of straight-chain alkanes, monobranched alkanes, and dibranched alkanes. Among these, dibranched alkanes not only have higher octane numbers but also burn more completely, serving as the "ultimate blending component" for future gasoline upgrades. Monobranched and straight-chain alkanes, however, have lower octane numbers and need to be separated from the isomerized oil to further increase the octane number of the gasoline. However, these hydrocarbon isomers are similar in molecular size and boiling point, making separation and purification difficult.

[0003] Anion-functionalized ultraporous materials are a class of highly ordered porous materials formed by coordination bonds between inorganic anions, organic ligands, and metal nodes. The inner surface of the pores in these materials is rich in high-density inorganic anions, providing abundant interaction sites and exhibiting excellent molecular recognition capabilities. Furthermore, the pore structure and size of these materials are finely tunable, and their excellent designability and molecular recognition capabilities enable them to demonstrate superior separation performance in adsorption separation, making them promising for the efficient separation of isomerized oils. However, the pore structure, intrapore chemical properties, and adsorption separation performance of anion-functionalized ultraporous materials are closely related to the types of organic ligands and metal ions. Designing novel structures for these materials is crucial for their application, but the design and preparation process is challenging.

[0004] Patent specification CN111575047A discloses a method for separating isomerized oils, and patent specification CN112645788A discloses a method for separating 2,2-dimethylbutane and 2,3-dimethylbutane. Both patent technologies use flexible, fluorinated anion-hybrid porous materials as separation adsorbents, employing 1,2-dipyridineacetylene or 4,4'-bipyridine as the organic ligand. These two patent technologies have achieved good separation results, but further improvement is needed. Summary of the Invention

[0005] This invention provides an anion-functionalized microporous material that has a large adsorption capacity for low-octane straight-chain and monobranched alkanes, but a small adsorption capacity for high-octane dibranched alkanes. It can be used for the separation of isomerized oils to obtain high-octane gasoline.

[0006] An anion-functionalized ultraporous material is self-assembled from organic ligands, inorganic fluorine-containing anions, and metal ions via coordination bonds, and its general formula is ML-AO. x F 6-x x is 0, 1, or 2, where:

[0007] Metal ion M is Fe 2+ Co 2+ Ni 2+ Cu 2+ Zn 2+ Any one of them;

[0008] The structural formula of the organic ligand L is as follows:

[0009]

[0010] Among them, R1, R2, R3, R4, R5, R6, R7, and R8 are each independently selected from any one of H, F, Cl, Br, I, -CH3, -NH2, -OH, and -COOH;

[0011] Inorganic fluoride anion AO x F 6-x SiF6 2- GeF6 2- ZrF6 2- SnF6 2- TiF6 2- ,NbOF5 2- TaOF5 2- WO2F4 2- MoO2F4 2- Any one of them.

[0012] The anion-functionalized ultraporous material ML-AO x F 6-x The metal M is hexacoordinate, with each metal M coordinating with the N-coordinates of four 3,3'-bipyridine ligands and the F-coordinates of two inorganic fluorine-containing anions, exhibiting a one-dimensional through-hole structure with an average pore size of 0.3–0.9 nm. As in Example 1 of this invention, 3,3'-bipyridine is used as the organic ligand, and SiF6… 2- Cu is an inorganic fluoride anion. 2+ Crystal structure diagram of anion-functionalized ultraporous materials constructed for metal ions is shown below. Figure 1 and Figure 2 As shown.

[0013] The preparation method of the anion-functionalized ultraporous material includes the following steps:

[0014] (1) Dissolve the metal ion inorganic salt and the inorganic fluorine-containing anionic compound in solvent A to obtain solution A, and dissolve the organic ligand L in solvent B to obtain solution B;

[0015] (2) Add solution A dropwise to solution B, and stir the reaction using interfacial diffusion or hydrothermal method. The resulting material is soaked in solvent C, washed, filtered, and dried to obtain the anion-functionalized ultraporous material.

[0016] Preferably, the inorganic salt containing the metal ion is any one of chloride, fluoride, nitrate, or tetrafluoroborate.

[0017] Preferably, solvent A and solvent B are each independently one or more of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, chloroform, dimethyl sulfoxide, ethylene glycol, and water; and solvent C is methanol or ethanol.

[0018] Preferably, in step (2), the ratio of metal ion inorganic salt to inorganic fluorine-containing anionic compound is 1 to 2:1, and the concentration of solution A is 0.05 to 2 mmol / L, based on the concentration of metal ion. The ratio of organic ligand L to metal ion inorganic salt is 1 to 2:1, and the concentration of solution B is 0.05 to 4 mmol / L.

[0019] Preferably, the reaction temperature of the interfacial diffusion method or hydrothermal method in step (2) is 10 to 150°C, and the reaction time is 2 min to 72 h.

[0020] Preferably, the washing, filtering, and drying process involves washing and filtering with methanol or ethanol, then soaking in methanol for 40–50 hours, followed by vacuum desorption and purging with flowing gas for drying at a temperature of 25–150°C for 6–72 hours.

[0021] This invention also provides the application of the aforementioned anion-functionalized ultraporous material in the adsorption and separation of isomerized oil.

[0022] The anion-functionalized ultraporous material provided by this invention can be applied to the selective adsorption and separation of C5-C8 alkane isomers. It can preferentially adsorb low-octane alkanes (straight-chain and single-branched alkanes) to obtain pure high-octane alkanes (multi-branched alkanes), thereby efficiently improving the octane number of gasoline.

[0023] The anion-functionalized ultraporous material provided by this invention is rich in high-density fluorine-containing anions, exhibiting excellent molecular recognition capabilities. Simultaneously, by altering the types of inorganic fluorine-containing anions and metal ions, the pore size and internal chemical environment of this material can be precisely controlled. This allows the series of materials to preferentially recognize low-octane straight-chain and monobranched alkanes from isomerized oils, exhibiting high adsorption capacity, while showing low adsorption capacity or even size sieving for high-octane multibranched alkanes, thus achieving efficient separation of isomerized oils. The results of Example 1 of this invention show that, under the same conditions, the anion-functionalized ultraporous material provided by this invention has a significantly higher adsorption capacity for straight-chain alkanes such as n-hexane and monobranched alkanes such as 2-methylpentane and 3-methylpentane than for dibranched alkanes.

[0024] Compared with the prior art, the beneficial effects of this invention are as follows:

[0025] 1) The anion-functionalized ultraporous material provided by the present invention has the advantages of adjustable pore structure and adjustable interaction force with adsorbate molecules, and can selectively recognize gas molecules to achieve selective adsorption and separation of mixed gases.

[0026] 2) The anion-functionalized ultraporous material provided by this invention has the advantages of simple synthesis method, mild conditions, and easy batch preparation;

[0027] 3) The anion-functionalized ultraporous material provided by this invention can separate high-octane dibranched alkanes from low-octane n-alkanes and monobranched alkanes in isomerized oil, thereby increasing the octane number of gasoline.

[0028] 4) The anion-functionalized ultraporous material provided by this invention is easy to regenerate as an adsorbent, can be reused, has low energy consumption, and is suitable for industrial application. Attached Figure Description

[0029] Figure 1 The crystal structure diagram of the anion-functionalized ultraporous material obtained in Example 1 is shown.

[0030] Figure 2 The crystal structure diagram of the anion-functionalized ultraporous material obtained in Example 1 is shown.

[0031] Figure 3 The X-ray diffraction (XRD) curves of the anion-functionalized ultraporous material obtained in Example 1 are shown.

[0032] Figure 4 The XRD curve of the anion-functionalized ultraporous material obtained in Example 2;

[0033] Figure 5 Thermogravimetric analysis (TGA) curves of the anion-functionalized ultraporous material obtained in Example 1;

[0034] Figure 6 The adsorption isotherms of the anion-functionalized ultraporous material obtained in Example 1 for n-hexane, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane and 2,3-dimethylbutane at 298 K are shown.

[0035] Figure 7 The adsorption isotherms of the anion-functionalized ultraporous material obtained in Example 2 for n-hexane, 2-methylpentane and 2,3-dimethylbutane at 298 K are shown.

[0036] Figure 8 The adsorption isotherms of the anion-functionalized ultraporous material obtained in Example 3 for n-hexane, 2-methylpentane and 2,3-dimethylbutane at 298 K are shown.

[0037] Figure 9 The adsorption isotherms of the anion-functionalized ultraporous material obtained in Example 4 for n-hexane, 2-methylpentane and 2,3-dimethylbutane at 298 K are shown.

[0038] Figure 10 The breakthrough curve of the anion-functionalized ultraporous material obtained in Example 1 for a mixture of n-hexane, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane and 2,3-dimethylbutane at 298 K.

[0039] Figure 11 SiF6 uses 4,4'-bipyridine as the organic ligand. 2- Cu is an inorganic anion. 2+ Crystal structure diagram of SIFSIX-1-Cu, an anion-functionalized ultraporous material constructed for metal nodes;

[0040] Figure 12 The breakthrough curves of SIFSIX-1-Cu at 298 K for a mixture of n-hexane, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane, and 2,3-dimethylbutane. Detailed Implementation

[0041] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Operating methods not specifically specified in the following embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0042] Example 1

[0043] 1 mmol Cu(BF4)2 and 1 mmol (NH4)2SiF6 were dissolved in 10 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 8 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material SIFSIX-33-Cu.

[0044] The crystal structure diagram of the SIFSIX-33-Cu anion-functionalized ultraporous material obtained in Example 1 is shown below. Figure 1 and Figure 2 As shown, in SIFSIX-33-Cu, the metallic Cu is six-coordinated, with each Cu atom coordinated to the N atoms of four 3,3'-bipyridine ligands and to the F atoms of two fluorine-containing anions. Because the nitrogen atoms at the two coordination nodes on the 3,3'-bipyridine are not aligned, the four coordinated copper atoms at each pore are not in the same plane, exhibiting a staggered coordination pattern. This results in SIFSIX-33-Cu having a one-dimensional, straight-through dumbbell-shaped pore structure, with a minimum pore diameter of 0.4 nm and a maximum pore diameter of 0.76 nm. In contrast, using 4,4'-bipyridine as the organic ligand, SiF6… 2- Cu is an inorganic anion. 2+ The crystal structure diagram of SIFSIX-1-Cu, anion-functionalized ultraporous material constructed for metal nodes, is shown below. Figure 11 As shown, since the two coordination nodes of nitrogen atoms on 4,4'-bipyridine are in a straight line, the four copper atoms in each pore of SIFSIX-1-Cu are in the same plane, forming a square one-dimensional pore structure with a pore size of 0.8 nm.

[0045] The powder X-ray diffraction of the SIFSIX-33-Cu material obtained in Example 1 was tested, and the results are as follows: Figure 3 As shown, the peak positions and relative intensities of the material's spectrum are basically consistent with those of the simulated crystal spectrum, and the peaks are sharp, indicating that the SIFSIX-33-Cu material prepared by this invention has high purity and good crystallinity.

[0046] The thermogravimetric analysis of SIFSIX-33-Cu obtained in Example 1 was performed, and the results are as follows: Figure 5 As shown, the thermal stability of the SIFSIX-33-Cu material prepared by the invention reaches 258℃.

[0047] The adsorption isotherms of the SIFSIX-33-Cu material obtained in Example 1 for single components of n-hexane, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane, and 2,3-dimethylbutane at 298 K were tested, and the results are as follows: Figure 6As shown in the figure. Test results indicate that SIFSIX-33-Cu exhibits strong interactions with low-octane straight-chain alkanes (n-hexane) and monobranched alkanes (2-methylpentane and 3-methylpentane), demonstrating high adsorption capacity. At 298 K and 16 kPa, the adsorption capacities are 1.89 mmol / g, 1.67 mmol / g, and 1.68 mmol / g, respectively. In contrast, SIFSIX-33-Cu shows adsorption capacities of only 0.55 mmol / g and 0.11 mmol / g for high-octane branched alkanes 2,2-dimethylbutane and 2,3-dimethylbutane. Therefore, the anion-functionalized ultraporous material provided by this invention can achieve the separation of isomerized oils to obtain high-octane branched alkanes.

[0048] The SIFSIX-33-Cu obtained in Example 1 was packed into a 5 cm adsorption column. A mixture of hexane, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane, and 2,3-dimethylbutane (molar ratio 1:1:1:1:1) vapors was introduced into the adsorption column at 1 mL / min at 25 °C. The breakthrough curve is shown below. Figure 10 As shown, high-octane dibranched alkanes (2,2-dimethylbutane and 2,3-dimethylbutane) elute first, and a high-octane mixed gas can be obtained within 40 minutes. Adsorption is stopped when hexane breaks through, and the adsorption column is purged with nitrogen. The adsorption column is recyclable. Under the same conditions, SiF6 with 4,4'-bipyridine as the organic ligand was tested. 2- Cu is an inorganic anion. 2+ The adsorption and separation performance of isomerized oil by SIFSIX-1-Cu, an anion-functionalized ultraporous material constructed for metal nodes, is shown in the following results: Figure 12 As shown, the dibranched alkane 2,3-dimethylbutane and the monobranched alkane (2-methylpentane and 3-methylpentane) elute from the sample column almost simultaneously. Therefore, SIFSIX-1-Cu cannot separate the 2,3-dimethylbutane with the highest octane number from the monobranched alkane with the lower octane number.

[0049] Example 2

[0050] 1 mmol NiNbOF5 was dissolved in 10 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 12 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anionic functionalized ultraporous material NbOFFIVE-33-Ni.

[0051] The powder X-ray diffraction of the NbOFFIVE-33-Ni material obtained in Example 2 was tested, and the results are as follows: Figure 4 As shown.

[0052] The adsorption isotherms of the NbOFFIVE-33-Ni material obtained in Example 2 for single components of n-hexane, 2-methylpentane, and 2,3-dimethylbutane at 298 K were tested, and the results are as follows: Figure 7 As shown in the figure. Test results indicate that NbOFFIVE-33-Ni can separate hexaalkyl molecules one by one based on their degree of branching. At 298 K and 16 kPa, the adsorption capacities of NbOFFIVE-33-Ni for n-hexane, 2-methylpentane, and 2,3-dimethylbutane are 1.71 mmol / g, 1.35 mmol / g, and 0.81 mmol / g, respectively. Therefore, the anion-functionalized ultraporous material NbOFFIVE-33-Ni provided by this invention can selectively separate the high-octane-number dibranched alkane 2,3-dimethylbutane from a mixture of n-hexane, 2-methylpentane, and 2,3-dimethylbutane.

[0053] Example 3

[0054] 1 mmol Cu(BF4)2 and 1 mmol (NH4)2TiF6 were dissolved in 10 mL of water, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL of ethylene glycol. The mixture was stirred at 65 °C for 8 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material TIFSIX-33-Cu.

[0055] The adsorption isotherms of the TIFSIX-33-Cu material obtained in Example 3 for single components of n-hexane, 2-methylpentane, and 2,3-dimethylbutane at 298 K were tested, and the results are as follows: Figure 8 As shown in the figure. Test results indicate that TIFSIX-33-Cu can separate hexaalkyl molecules one by one based on their degree of branching. At 298 K and 16 kPa, the adsorption capacities of TIFSIX-33-Cu for n-hexane, 2-methylpentane, and 2,3-dimethylbutane are 1.76 mmol / g, 1.52 mmol / g, and 0.82 mmol / g, respectively. Therefore, the anion-functionalized ultraporous material TIFSIX-33-Cu provided by this invention can selectively separate the high-octane-number dibranched alkane 2,3-dimethylbutane from a mixture of n-hexane, 2-methylpentane, and 2,3-dimethylbutane.

[0056] Example 4

[0057] 1 mmol Cu(NO3)2 and 1 mmol (NH4)2GeF6 were dissolved in 10 mL of water, and 1.5 mmol of 3,3'-bipyridine was dissolved in 20 mL of ethylene glycol. The mixture was stirred at 65 °C for 3 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material GeFSIX-33-Cu.

[0058] The adsorption isotherms of the GeFSIX-33-Cu material obtained in Example 4 for single components of n-hexane, 2-methylpentane, and 2,3-dimethylbutane at 298 K were tested, and the results are as follows: Figure 9 As shown in the figure. Test results indicate that GeFSIX-33-Cu can separate hexaalkyl molecules one by one based on the difference in the degree of branching. At 298 K and 16 kPa, the adsorption capacities of GeFSIX-33-Cu for n-hexane, 2-methylpentane, and 2,3-dimethylbutane are 1.76 mmol / g, 0.68 mmol / g, and 0.27 mmol / g, respectively. Therefore, the anion-functionalized ultraporous material GeFSIX-33-Cu provided by this invention can selectively separate the high-octane-number dibranched alkane 2,3-dimethylbutane from a mixture of n-hexane, 2-methylpentane, and 2,3-dimethylbutane.

[0059] Example 5

[0060] 1 mmol Ni(BF4)2 and 1 mmol (NH4)2TiF6 were dissolved in 10 mL of water, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL of ethylene glycol. The mixture was stirred at 65 °C for 3 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material TiFSIX-33-Ni.

[0061] Example 6

[0062] 1 mmol CoF2 and 1 mmol (NH4)2GeF6 were dissolved in 10 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 3 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material GeFSIX-33-Co.

[0063] Example 7

[0064] 1 mmol Zn(NO3)2 and 1.12 mmol (NH4)2TiF6 were dissolved in 5 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 6 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anionic functionalized ultraporous material TiFSIX-33-Zn.

[0065] Example 8

[0066] 1 mmol Ni(BF4)2 and 1.12 mmol (NH4)2ZrF6 were dissolved in 10 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 6 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anionic functionalized ultraporous material ZrFSIX-33-Ni.

[0067] Example 9

[0068] 1 mmol CuF2 and 1.12 mmol (NH4)2SnF6 were dissolved in 20 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 6 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material SnFSIX-33-Cu.

[0069] Example 10

[0070] 1 mmol Fe(NO3)2 and 1.12 mmol (NH4)2SiF6 were dissolved in 5 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 6 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material SiFSIX-33-Fe.

[0071] Example 11

[0072] 1 mmol CuTaOF5 was dissolved in 10 mL methanol, and 1.5 mmol 3,3'-bipyridine was dissolved in 20 mL ethylene glycol. The mixture was stirred at 65 °C for 12 h. The resulting slurry was filtered and activated under vacuum at 80 °C for 24 h to obtain the anion-functionalized ultraporous material TaOFFIVE-33-Cu.

[0073] Furthermore, it should be understood that after reading the above description of the present invention, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims.

Claims

1. The application of anion-functionalized ultraporous material in the adsorption and separation of isomerized oil, characterized in that, The anion-functionalized ultraporous material is composed of organic ligands, inorganic fluorine-containing anions, and metal ions self-assembled through coordination bonds, and its general formula is ML-AO. x F 6-x , x is 0, where: Metal ion M is Cu 2+ ; The structural formula of the organic ligand L is as follows: Among them, R1, R2, R3, R4, R5, R6, R7 and R8 are H; Inorganic fluoride anion AO x F 6-x SiF6 2- ; The anion-functionalized ultraporous material is used for the adsorption and separation of n-hexane, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane and 2,3-dimethylbutane, and can separate 2,3-dimethylbutane with the highest octane number from single-branched alkanes with low octane numbers.

2. The application according to claim 1, characterized in that, The anion-functionalized ultraporous material has a one-dimensional through-hole structure with an average pore size of 0.3~0.9 nm.

Citation Information

Patent Citations

  • Separation method of 2, 2-dimethylbutane and 2, 3-dimethylbutane

    CN112645788A

  • Separation method of isomerized oil

    CN111575047A

  • Application of ionic hybrid porous material in separation of cyclohexene and cyclohexane and preparation method of ionic hybrid porous material

    CN114870806A